2021
DOI: 10.4236/ojanes.2021.111002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Ibuprofen on Ischemia-Reperfusion Injury Following Perioperative Tourniquet in Patients Undergoing Total Knee Arthroplasty

Abstract: Oxidative stress occurs in the organism with ischemia due to tourniquet use and subsequent reperfusion. Oxidative stress increases postoperative morbidity. Some Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) perform their anti-inflammatory effects in part by binding or inhibiting their formation of active oxygen radicals at the site of inflammation. In this study, we aimed to evaluate the effect of IV ibuprofen on ischemia-reperfusion injury (IRI) in patients undergoing total knee arthroplasty over oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…This indicated that the drug adversely affected the organism to fight oxidative stress and it should be taken into account in the drug choice for postoperative analgesia. 18 Similar to this study, the NT and TT levels were significantly decreased in ibuprofen pretreated patients in our study. However, no significant change was recorded in terms of disulfide level in all measurement points.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This indicated that the drug adversely affected the organism to fight oxidative stress and it should be taken into account in the drug choice for postoperative analgesia. 18 Similar to this study, the NT and TT levels were significantly decreased in ibuprofen pretreated patients in our study. However, no significant change was recorded in terms of disulfide level in all measurement points.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the NT and TT values were significantly decreased in this study, thiol/disulfide, disulfide/ NT, and disulfide/total levels showed no significant changes. This indicated that the drug adversely affected the organism to fight oxidative stress and it should be taken into account in the drug choice for postoperative analgesia 18 . Similar to this study, the NT and TT levels were significantly decreased in ibuprofen pretreated patients in our study.…”
Section: Discussionsupporting
confidence: 86%